2024
DOI: 10.23822/eurannaci.1764-1489.289
|View full text |Cite
|
Sign up to set email alerts
|

A real life cohort of mepolizumab treatment in severe eosinophilic asthma

Abstract: Background: Mepolizumab, a monoclonal antibody that interacts with IL-5, was the first anti-IL-5 approved for uncontrolled severe eosinophilic asthma. In several randomised, placebocontrolled trials, treatment with mepolizumab has shown a significant improvement in asthma symptoms and the need to use of oral corticosteroids (OCS). Several studies have correlated blood levels of eosinophil cationic protein (ECP) with the degree of eosinophilic inflammation, which could make it an indirect marker of eosinophilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…8 Eosinophil cationic protein (ECP), also known as RNase A family 3 (RNASE3), has been widely described and standardized as a marker of tissue eosinophilia and eosinophil activation. 9 The biological properties and clinical role of ECP have been demonstrated. Jin reported that NPs patients had higher concentrations of ECP in nasal secretions than healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…8 Eosinophil cationic protein (ECP), also known as RNase A family 3 (RNASE3), has been widely described and standardized as a marker of tissue eosinophilia and eosinophil activation. 9 The biological properties and clinical role of ECP have been demonstrated. Jin reported that NPs patients had higher concentrations of ECP in nasal secretions than healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The serum levels of ECP have been linked to the degree of eosinophilic inflammation, suggesting that it could be an indirect marker of eosinophilic activity [ 15 ]. The levels of eosinophil cationic protein (ECP) were also deemed to be a reliable prognostic indicator for the recurrence of nasal polyps following surgical intervention.…”
Section: Introductionmentioning
confidence: 99%